2020
DOI: 10.3390/en13112866
|View full text |Cite
|
Sign up to set email alerts
|

Power-Efficient Driver Circuit for Piezo Electric Actuator with Passive Charge Recovery

Abstract: Piezoelectric actuation is a promising principle for insect-scaled robots. A major concern while utilizing a piezoelectric actuator is energy loss due to its parasitic capacitance. In this paper, we propose a new concept to recover the charge stored in the parasitic capacitance; it requires only three additional lightweight passive components: two diodes and a resistor. The advantages of our concept are its small additional mass and simple operating procedure compared with existing charge recovery circuits. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…During the experiments, it was found that the relation between the output voltage and the measured position had a factor of 4. The performance of each framework was compared using the integral of the absolute magnitude of the error (IAE) over time as a metric, which has the expression of Equation (2). The use of the error magnitude in the integral results in a sensitive expression either for positive or negative values.…”
Section: Control Structurementioning
confidence: 99%
See 1 more Smart Citation
“…During the experiments, it was found that the relation between the output voltage and the measured position had a factor of 4. The performance of each framework was compared using the integral of the absolute magnitude of the error (IAE) over time as a metric, which has the expression of Equation (2). The use of the error magnitude in the integral results in a sensitive expression either for positive or negative values.…”
Section: Control Structurementioning
confidence: 99%
“…Piezoelectric actuators (PEAs) are positioning systems which have been widely used in the field of micro-and nano-positioning due to their high displacement resolution (around the micrometer), large actuation force (typically several hundred of Newtons), high speed response and vast stiffness. They had also been employed in applications such as scanning probe microscopes (SPM), computer components, micro-manipulators, machine tools and energy recovery [1,2]. However, the biggest problem with PEAs are non-linearities due to the effects of hysteresis, creep, and vibrations, which can significantly degrade the system performance and even its stability.…”
Section: Introductionmentioning
confidence: 99%
“…Second, only a fraction of the input electric power is converted into mechanical work by the piezoelectric material. The rest is stored in the capacitive storage, which must be recovered to maximize the system's efficiency [34]. Third, piezoelectric materials suffer from huge nonlinearities, hysteresis and noticeable creep [30], resulting in that each given input provides an unexpected output.…”
Section: Piezoelectric Actuatorsmentioning
confidence: 99%
“…The blend is produced with the advantage of their size, which is an asset for the downsizing trend in actuators today. Due to these benefits, the applications are broad which includes energy harvesting [4], active vibration [5], motor design [6], etc. Furthermore, in recent years, the PEA has been a research aim for medical uses, such as drug delivery systems [7], micro grippers [8], spinal injection device [9], and orthodontic treatment [10].…”
Section: Introductionmentioning
confidence: 99%